Neuroepigenomics: Resources, Obstacles, and Opportunities - Satterlee, John S. (Neuroepigenetics, 2015)
Long-lived post-mitotic cells, such as the majority of human neurons, must respond effectively to ongoing changes in neuronal stimulation or microenvironmental cues through transcriptional and epigenomic regulation of gene expression. The role of epigenomic regulation in neuronal function is of fundamental interest to the neuroscience community, as these types of studies have transformed our understanding of gene regulation in post-mitotic cells. This perspective article highlights many of the resources available to researchers interested in neuroepigenomic investigations and discusses some of the current obstacles and opportunities in neuroepigenomics.